Redefining Femininity in The Ugly Stepsister (2025) : A Critical Discourse Analysis of Beauty Standards and Power Relations - Rafina Nuraisa; Aulia Rahmawati (International Journal of Social, Economic, and Business, 2026)
This study examines the discourse of femininity and beauty standards in the film The Ugly Stepsister using Sara Mills’ Critical Discourse Analysis. The research is based on the persistence of patriarchal beauty standards reproduced through popular narratives, particularly the Cinderella story. The film portrays Elvira as a woman who experiences social pressure to conform to ideal femininity in order to gain validation and acceptance. This study aims to analyze how femininity, body control, and power relations are represented through verbal, visual, and narrative aspects in the film. The research employs a descriptive qualitative method with Sara Mills’ approach focusing on subject-object positions and writer-reader positions. The findings reveal that the female body is constructed as an object of social discipline shaped by patriarchal values and beauty standards. Although Elvira is positioned as an active subject within the narrative, she simultaneously becomes the object of objectification and social pressure. The study also shows that beauty standards are reproduced not only by male characters but also through relationships among women. This research implies that film functions as a medium that both reproduces and reconstructs discourses surrounding femininity in popular culture.